Swedish Party Membership Survey 2015, complete dataset - Kölln, Ann-Kristin; Polk, Jonathan (University of Gothenburg, 2022)
In the early part of 2015, the party secretaries of six of the eight Swedish Riksdag parties (plus the Feminist Initiative as the only other Swedish party represented in the European Parliament) agreed to take part in an online survey of their memberships, which would be administered through the Laboratory of Opinion Research (LORE) at the University of Gothenburg.

In May, these party secretaries distributed individualized links to an otherwise identical web-survey to their members via email. All parties, except for the Social Democrats, sent out the survey to the entire membership list. The Social Democrats sent the survey to a large randomly drawn sample from their membership list. When it was closed on July 3, a total of 10,392 Swedish party members had completed the survey.

Purpose:

The purpose of the Swedish party membership survey is to allow researchers to investigate much more specific and rich questions about party members in Sweden. The survey questions are grouped into six modules: socio-demographic, general political attitudes, reasons for and extent of enrolment, position within the party, activism, and perception of role and attitudes towards membership. The questions were developed in consultation with the Members and Activists of Political Parties (MAPP) research group in order to facilitate cross-national comparisons.

The dataset is available as a SPSS file (.sav), a Nesstar Publisher project and as comma-separated values (.csv).

I början av 2015 sa partisekreterarna i sex av de svenska riksdagspartierna (plus Feministiskt Initiativ, som är det enda icke-riksdagspartiet representerat i Europaparlamentet) ja till att vara med och genomföra en nätbaserad enkät bland sina partimedlemmar. Undersökningen administrerades av Laboratory of Opinion Research (LORE) vid Göteborgs universitet.

I maj 2015 distribuerade partisekreterarna i respektive parti en personlig länk till sina medlemmar. Länken gick till en i övrigt identisk enkät. Alla partier utom Socialdemokraterna skickade enkäten till samtliga sina registrerade medlemmar. Socialdemokraterna skickade istället enkäten till ett stort, slumpmässigt urval av sina medlemmar. När enkäten stängde den 3 juli hade totalt 10.392 partimedlemmar svarat.

Syfte:

Syftet med den svenska partimedlemsundersökningen var att generera unik data som kommer att låta forskare undersöka svenskt partimedlemskap på nya sätt, med specifika frågor om medlemskap ställda till just partimedlemmar. Undersökningens frågor var grupperade i sex moduler: socio-demografi, allmänna politiska attitydfrågor, skäl till och längd av medlemskapet, position inom partiet, aktivism och uppfattningar om och attityder till medlemmarnas roll i partiet. Frågorna utvecklades i samarbete med forskargruppen Members and Activists of Political Parties (MAPP) för att möjliggöra jämförelser mellan länder.

Datasetet finns tillgängligt i SPSS-format (.sav), som ett Nesstar Publisher-projekt och som kommaseparerade värden (.csv).
Svenska partimedlemsundersökningen 2015, fullständigt dataset
Keywords: POLITICS; POLITIK; MEMBERSHIP; MEDLEMSKAP; DEMOCRACY; DEMOKRATI; PARTY POLITICS; PARTIPOLITIK; POLITICAL PARTIES; POLITISKA PARTIER; Political behaviour and attitudes; Politiska beteenden och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap